FUSION PLASMA NUCLEAR-PHYSICAL DIAGNOSTICS METHODS - Zhusupov, M. A.; Kabatayeva, R. S. (Recent Contributions to Physics, 2009)
In the article dt -plasma ion component nuclear-physical diagnostics problems by lithium isotopes injection are considered. Cross sections’ resonance structure of, reactions on 7Li and 6Li nuclei is determined by the structural peculiarities of the excited states of 11B and 10B nuclei, which have low values of -widths. Average rates and -quanta yield for the reactions have been calculated.
Keywords: plasma